Analisis Pola Komunikasi Personal Mahasiswa dalam Mengatasi Hambatan Interaksi Tatap Muka Pasca Ketergantungan Media Sosial - Rifky Dwi Fahrezy Harahap; Sabira Naisah Azzahra; Naufal Habib; Zaky Alfath (Universitas Muhammadiyah Sumatera Utara, 2026)
This study aims to analyze the interpersonal communication patterns of college students in facing barriers to face-to-face interaction influenced by dependence on social media. The development of digital technology has changed the way individuals communicate, where students tend to interact more actively through social media than in person. This has resulted in a shift in interpersonal communication patterns from face-to-face to mediated communication. This study uses a qualitative approach with descriptive methods to understand the phenomena occurring among college students. The results show that social media dependence affects the quality of interpersonal communication, such as a decline in direct communication skills, the emergence of barriers to social interaction, and a tendency to avoid face-to-face communication. In addition, phenomena such as Fear of Missing Out (FoMO) also strengthen students' attachment to social media, thereby increasing barriers to social interaction in the real world. Although social media provides convenience in communication, excessive use can reduce the quality of interpersonal relationships and emotional closeness between individuals. Therefore, awareness is needed in managing social media use to maintain a balance between online and face-to-face communication.